The Effect of Trichoderma Species on the Vegetative Growth Phase f Rice (Oryza sativa L.) in Gombe State - Abubakar Z. A; Ibrahim A.U; Kulawe D.; Ibrahim B. J. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The novel technologies in all areas of agriculture have improved agricultural production, but some modern practices affect the environment. The recent challenge faced by advanced farming is to achieve higher yields in environment-friendly manner. Thus, there is an immediate need to find eco-friendly solutions such as wider application of biocontrol agents. Among various types of species being used as biocontrol agents, including fungi and bacteria, fungal genus Trichoderma produces different kinds of enzymes which play a major role in biocontrol activity like degradation of cell wall, tolerance to biotic or abiotic stresses, hyphal growth etc. This experiment was conducted to find out the effects of Trichoderma viride on growth and yield of rice in Gombe State during May 2019 – September 2019. The experiment consisted of four treatments; (T1: NPK; T2: NPK CONTROL; T3: Trichoderma; T4: Trichoderma Control) laid out in completely randomized design (CRD) with three replications. The results showed that Trichoderma viride increased the plant height by 4.6 %, root weight (1.5 %), number of grains (3.8 %), grain yield (36.5 %) and biomass yield (2.7 %) over control; while root length (17.4 %), tiller number (10.8%) highlighted the negative impact of T. viride on rice plant. T. viride displayed antagonism with inorganic fertilizer. When T. viride and NPK were accompanied with manure, most of the growth and yield parameter showed the highest value. Though Trichoderma viride decreases several growth parameters, it still can be used as biofertilizer which increases the grain yield. Using T. viride with a full dose of NPK during sowing stage may not be efficient and economical in terms of productivity. Introducing farmyard manure to T. viride gives better yield than T. viride.